2007
DOI: 10.1002/lapl.200710042
|View full text |Cite
|
Sign up to set email alerts
|

Molecular processes and structural alterations in laser reshaping of cartilage

Abstract: Abstract:The effects of non-destructive laser irradiation on the structure and molecular processes in cartilage were studied using Raman microscopy, differential scanning calorimetry and biochemical analysis. A structural reorganization of the irradiated tissue similar to poliginization in polycrystalline solids was observed for the first time in a cartilage matrix. The difference in the Raman spectra of the irradiated and control samples was interpreted in term of a conformational alteration of glycosaminogly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…Varying exposure times for each Raman spectra and possible varying GAG concentrations at different cartilage locations may have resulted in the varying significance of the GAG contribution to the Raman spectra. 13,30 Despite previous studies suggesting that GAG possesses neither intrinsic nor form birefringence except under the influence of certain dyes, 42,43 our polarized Raman spectra [arrows in Figs. 4(b) and 4(c)] revealed a distinct parallel dichroism in the GAG-associated pyranose band at 1042 cm − 1 that may be useful for characterizing structural changes of cartilage in tissue.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Varying exposure times for each Raman spectra and possible varying GAG concentrations at different cartilage locations may have resulted in the varying significance of the GAG contribution to the Raman spectra. 13,30 Despite previous studies suggesting that GAG possesses neither intrinsic nor form birefringence except under the influence of certain dyes, 42,43 our polarized Raman spectra [arrows in Figs. 4(b) and 4(c)] revealed a distinct parallel dichroism in the GAG-associated pyranose band at 1042 cm − 1 that may be useful for characterizing structural changes of cartilage in tissue.…”
Section: Discussionmentioning
confidence: 61%
“…4(b)] show similar Raman spectral shapes and band positions to the rabbit nasal septa cartilage of rabbit, 30 except for the Raman band 957 cm − 1 associated with phosphate in the subchondral bone which was not reported. In our study, the phosphate Raman band (957 cm − 1 ) in the parallel polarized Raman spectra becomes visible after the porcine explants were impacted.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In several papers Raman spectroscopy and microspectroscopy have been employed to study pure collagen [3][4][5] as well as its presence in bone [6,7], cartilage [8], skin [9,10] and eye [11] tissues. In particular, Kazanci et al reported a polarization effect on the collagen-associated bands in Raman spectra of bone tissue [12].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the relative intensity ratio of this doublet, typically assigned to two amide III vibrations, has been usually employed as an important marker for collagen conformation [3,4,[6][7][8][9][10][11][15][16][17].…”
Section: Introductionmentioning
confidence: 99%